Banks' funding stress, lending supply and consumption expenditure - H. Evren Damar; Reint E. Gropp; Adi Mordel (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2019)
We employ a unique identification strategy linking survey data on household consumption expenditure to bank-level data to estimate the effects of bank funding stress on consumer credit and consumption expenditures. We show that households whose banks were more exposed to funding shocks report lower levels of nonmortgage liabilities. This, however, only translates into lower levels of consumption for low income households. Hence, adverse credit supply shocks are associated with significant heterogeneous effects.
urn:nbn:de:gbv:3:2-107557
Keywords: E21; E44; G01; G21; 330; credit supply; banking; financial crisis; consumption expenditure; liquid assets; consumption smoothing